Qualitative Assessment Availability and Competence of Health Professionals For the implementation of the SISCa at Comoro Community Health Centre, the Administrative Post of Dom Aleixo, Dili Municipality - Ligia Soriano Garcia, Carmen; Amaral Mali, Marcelo; Martins, Nelson (Rifa'Institute, 2024)
Introduction: To improve the health system and provide good health services to the community, experts have developed public health science to complement individual clinical services, focusing on individual diagnosis and treatment. SISCa was established to integrate various vertical programs into integrated, proactive, and active activities. Objective: This research aimed to assess the availability and competence of health professionals for SISCa in Comoro Community Health Center, Dom Aleixo Administrative Post, Dili Municipality. Method: The method used in this study is descriptive qualitative research, with data collection techniques such as observation, in-depth interviews, documentation, and recording. The data analysis technique is thematic analysis to find themes and analyze the data. Results and Discussion: The results showed that the implementation of SISCa will face problems such as human resources that will be limited, so when SISCa is implemented in the village the village health personnel must perform their duties through one. Looking at competence, many health personnel have not attended training including volunteers who have not attended training so when SISCa is implemented in the village health personnel provide services to the community according to some knowledge they have obtained through training and some experience. On the other hand, SISCa implemented Table-6 activities, but some did not implement them according to SISCa guidelines. Conclusion: that the availability of health professionals in CHC Comoro related to the implementation of SISCa will face problems such as human resources being limited allocated for the implementation of SISCa. On the other hand, many health professionals have not attended training including volunteers to implement SISCa has not been implemented according to SISCa guidelines.